(untitled) (The Pretoria Student Law Review, 2025)
The objectives of land reform, as per section 25 of the Constitution of the Republic of South Africa, 1996, are limited by conservative property conditions that maintain the status quo. As such, subjecting land expropriation to compensation is unjust and fortifies the brutality of apartheid and colonialism instead of addressing these historical injustices. This article argues that just and equitable nil compensation challenges the status quo. It will analyse Business Venture Investments 900 (Pty) Ltd v City of Ekurhuleni Metropolitan Municipality, to illustrate that just and equitable redress can be brought forth through a decolonial approach to nil compensation. It will then problematise Niklas Luhmann’s framework, contending that it perpetuates the status quo by undermining the role that positive law can play in correcting the injustices of the past. The article further asserts that the status quo is bolstered by positive law, such as South Africa’s Constitution, which helps keep marginalised groups landless.